A Scripture-formed Communion? Possibilities and Prospects after Lambeth, ACC, and General Convention - Wright, N. T. (Journal of Anglican studies, 2009)
The question of the authority, use and relevance of Scripture in today’s Anglican Communion needs to be addressed more thoroughly. All authority is God’s authority, and the question of Scripture’s authority needs to be reframed in that light: God is not merely providing information and instruction, but taking forward his Kingdom-project, and Scripture is not merely a witness to that but also a necessary agent, equipping God’s people for their tasks. Various questions then emerge in a new light: we need an integrated, layered, and nuanced vision of the whole Scripture, foregrounding the gospel challenge of new creation and recognizing the inadequacy of some standard slogans such as Jesus’ supposed slackening of the law. In particular, the biblical basis of ‘covenant’ needs further exploration, and the whole communion should embrace a much richer practice of Scripture reading and study to face the challenges of tomorrow’s world.